HIV-1 Single-Stranded RNA Induces CXCL13 Secretion in Human Monocytes via TLR7 Activation and Plasmacytoid Dendritic Cell–Derived Type I IFN - Cohen, Kristen W; Dugast, Anne-Sophie; Alter, Galit; McElrath, M Juliana; Stamatatos, Leonidas (The Journal of immunology (1950), 2015)
Elevated levels of the chemokine CXCL13 have been observed in the plasma of chronically HIV-1–infected subjects and have been correlated with plasma viremia, which in turn has been linked to progressive dysregulation of humoral responses. In this study we sought to identify mechanisms of CXCL13 induction in response to HIV-1 infection. Plasma levels of CXCL13 in HIV-1–infected antiretroviral therapy–naive subjects correlated with viral load and were higher compared with antiretroviral therapy–treated HIV-1–infected and HIV-1–uninfected subjects. To elucidate the relationship between HIV-1 viremia and CXCL13 plasma levels, PBMCs from uninfected donors were stimulated with HIV-1 infectious virions, HIV-1 ssRNA, TLR 7 and 8 agonists, or IFN-α. The cellular sources of CXCL13 were determined by intracellular cytokine staining of cell populations. CXCL13 was produced by monocytes after stimulation with TLR 7 and 8 ligands or HIV-1–derived ssRNA. CXCL13 production by monocytes required TLR7 activation of plasmacytoid dendritic cells and secretion of type I IFN. IFN-α alone was sufficient to induce CXCL13 expression in human monocytes. In sum, we identified a novel mechanism of HIV-1–induced CXCL13 secretion—one caused by TLR7 induction of type I IFN by plasmacytoid dendritic cells and subsequent IFN stimulation of monocytes. Our findings are relevant in understanding how HIV-1 infection leads to immune dysregulation and provide the opportunity to develop and test potential therapeutic interventions.